Effects of PDGF-BB delivery from heparinized collagen sutures on the healing of lacerated chicken flexor tendon in vivo. (November 2017) - Younesi, Mousa; Knapik, Derrick M.; Cumsky, Jameson; Donmez, Baris Ozgur; He, Ping; Islam, Anowarul; Learn, Greg; McClellan, Philip; Bohl, Michael; Gillespie, Robert J.; Akkus, Ozan
Graphical abstract: Abstract: Flexor tendon lacerations are traditionally repaired by using non-absorbable monofilament sutures. Recent investigations have explored to improve the healing process by growth factor delivery from the sutures. However, it is difficult to conjugate growth factors to nylon or other synthetic sutures. This study explores the performance of a novel electrochemically aligned collagen suture in a flexor tendon repair model with and without platelet derived growth factor following complete tendon laceration in vivo . Collagen suture was fabricated via electrochemical alignment process. Heparin was covalently bound to electrochemically aligned collagen sutures (ELAS) to facilitate affinity bound delivery of platelet-derived growth factor-BB (PDGF-BB). Complete laceration of the flexor digitorum profundus in the third digit of the foot was performed in 36 skeletally mature White Leghorn chickens. The left foot was used as the positive control. Animals were randomly divided into three groups: control specimens treated with standard nylon suture (n = 12), specimens repaired with heparinated ELAS suture without PDGF-BB (n = 12) and specimens repaired with heparinated ELAS suture with affinity bound PDGF-BB (n = 12). Specimens were harvested at either 4 weeks or 12 weeks following tendon repair. Differences between groups were evaluated by the degree of gross tendon excursion, failure load/stress, stiffness/modulus, absorbed energy at failure, elongation/strain at failure. Quantitative histological scoring was performed to assess cellularity and vascularity. Closed flexion angle measurements demonstrated no significant differences in tendon excursion between the study groups at 4 or 12 weeks. Biomechanical testing showed that the group treated with PDGF-BB bound heparinated ELAS suture had significantly higher stiffness and failure load (p < 0.05) at 12-weeks relative to both heparinated ELAS suture and nylon suture. Similarly, the group treated with PDGF-BB bound suture had significantly higher ultimate tensile strength and Young's modulus (p < 0.05) at 12-weeks relative to both ELAS suture and nylon suture. Compared to nylon controls, heparinized ELAS with PDGF-BB improved biomechanics and vascularity during tendon healing by 12-weeks following primary repair. The ability of ELAS to deliver PDGF-BB to the lacerated area of tendon presents investigators with a functional bioinductive platform to improve repair outcomes following flexor tendon repair. Statement of significance: A high strength aligned collagen suture was fabricated via linear electrocompaction and heparinized for prolonged delivery of PDFG-BB. When it was used to suture a complete lacerated flexor tendon in a chicken model controlled release of the PDGF-BB improved the strength of treated tendon after 12 weeks compared to tendon sutured with commercial nylon suture. Furthermore, Collagen suture with affinity bound PDGF-BB enhanced the vascularization and remodeling of lacerated tendon when it compare to synthetic nylon suture. Overall, electrocompacted collagen sutures holds potential to improve repair outcome in flexor tendon surgeries by improving repair strength and stiffness, vascularity, and remodeling via sustained delivery of the PDGF-BB. The bioinductive collagen suture introduces a platform for sustained delivery of other growth factors for a wide-array of applications.